Short Stature on a Boy: Mosaicism with an Isodicentric Y Chromosome - Catarina Silvestre; Juliette Dupont; Rosário Silveira Santos; Brígida Robalo; Carla Pereira; Maria Lurdes Sampaio (Case Reports in Pediatrics)
Mosaicism brings great variability into the clinical expression of numerical and structural chromosomal abnormalities. The phenotypic variability of 45,X/46,XY mosaicism extends from Turner syndrome to apparently physically normal males. We present a case of a 14-year-old adolescent with short stature and delayed puberty, who was admitted in a Paediatric Endocrinology outpatient clinic. After a careful investigation, he was found to have a 45,X/46,X,idic(Y)(p11.32) mosaicism. This case report emphasizes the wide range of etiologies that can be involved in short stature and that chromosomal study is an important tool when firstly approaching males with short stature, avoiding unnecessary tests. There is an important clinical need for gonadal follow-up in this situation and for support in the decision about sex of rearing and sex orientation, when justifiable.